2003
DOI: 10.1046/j.1440-1819.2003.01080.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between electroencephalography and heart rate variability during sleep

Abstract: It is known that autonomic nervous activities change in correspondence with sleep stages. However, the characteristics of continuous fluctuations in nocturnal autonomic nerve tone have not been clarified in detail. The study aimed to determine the possible correlation between the electroencephalogram (EEG) and autonomic nervous activities, and to clarify in detail the nocturnal fluctuations in autonomic nerve activities. Overnight EEGs and electrocardiograms of seven healthy males were obtained. These EEGs wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
81
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 151 publications
(99 citation statements)
references
References 29 publications
7
81
3
1
Order By: Relevance
“…The findings of this study suggested that nighttime workers would seem to have higher cardiac sympathetic regulations attributable to long-term night shift working, which may explain why they have been found to have higher rates of cardiac disorders. Sleep assigned according to a predetermined laboratory schedule can sometimes fail to reflect the habitual sleeping time (27)(28)(29). Our design allowed nurses to sleep spontaneously in their own beds, in privacy, and according to their flexible night shift sleeping schedule.…”
Section: Figure1 Electroencephalographic Delta-power During Periods mentioning
confidence: 99%
“…The findings of this study suggested that nighttime workers would seem to have higher cardiac sympathetic regulations attributable to long-term night shift working, which may explain why they have been found to have higher rates of cardiac disorders. Sleep assigned according to a predetermined laboratory schedule can sometimes fail to reflect the habitual sleeping time (27)(28)(29). Our design allowed nurses to sleep spontaneously in their own beds, in privacy, and according to their flexible night shift sleeping schedule.…”
Section: Figure1 Electroencephalographic Delta-power During Periods mentioning
confidence: 99%
“…For instance, EEG power spectral density relates to VHR indices (Otzenberger et al, 1997(Otzenberger et al, , 1998Ehrhart et al, 2000;Brandenberger et al, 2001;Ako et al, 2003). However, the cerebral correlates of VHR during sleep needs to be further characterized, anatomically refined and described separately for NREMS and REMS.…”
Section: Introductionmentioning
confidence: 99%
“…Period amplitude analysis has been applied and compared with power spectral analysis for all-night recordings [194]. The investigation of the correlation between spectral EEG activity and heart rate variability during sleep shows that sympathetic nervous system activity continuously fluctuates in accordance with sleep deepening and lightening [195]. Finally, by comparing the predicted rhythm to the actual EEG at each sample with the rhythm of the previous one in specific frequency ranges, it is possible to construct microcontinuity parameters with physiological implications sensitive to sleep and less sensitive to artefacts [196].…”
Section: Digital Data Processingmentioning
confidence: 99%